Antimicrobial Activity and Action Approach of the Olive Oil Polyphenol Extract Against Listeria monocytogenes - Guo, Ling; Sun, Qi; Gong, Shaoying; Bi, Xue; Jiang, Wen; Xue, Wei; Fei, Peng (Frontiers in Microbiology, 2019)
Olive oil polyphenols extract (OOPE) has antimicrobial properties against foodborne pathogens, without much currently researched on the effects against Listeria monocytogenes. The targets of antimicrobial action of OOPE were studied using different physiological indices: minimum inhibitory concentration (MIC), intracellular ATP concentration, cell membrane potential, content of bacterial protein and cell morphology. It was found that OOPE had antimicrobial activity against L. monocytogenes tested with MICs of 1.25 mg/mL. Measurements of the lower intracellular ATP and higher membrane potential suggested the disruptive action of OOPE on cytoplasmic membranes. The results of sodium dodecyl sulfate-polyacrylamide gel electrophoresis and transmission electron microscope showed OOPE could cause leakage of proteins in the bacteria cells, pore-formation with damaging cell membranes and promoting the release of bacteria cell constituents. The results proved the potential of OOPE as a green and sustainable source of a new antimicrobial agent against L. monocytogenes.